2017
DOI: 10.3791/55872
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic, Heart Rate, and Galvanic Skin Response Assessment for an Advertising Perception Study: Application to Antismoking Public Service Announcements

Abstract: The evaluation of advertising, products, and packaging is traditionally performed through methods based on self-reports and focus groups, but these approaches often appear poorly accurate in scientific terms. Neuroscience is increasingly applied to the investigation of the neurophysiological bases of the perception of and reaction to commercial stimuli to support traditional marketing methods. In this context, a particular sector or marketing is represented by public service announcements (PSAs). The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 76 publications
(106 reference statements)
1
57
0
7
Order By: Relevance
“…Based on our literature review, we identified four autonomic EEG indices that have been utilized for evaluating the reactions of the people in marketing stimuli: (1) the approach-withdrawal (AW) motivation index; (2) effort index; (3) choice index; and (4) valence. Such indices assist marketers in understanding customer responses to products [30,31].…”
Section: Eeg Indicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on our literature review, we identified four autonomic EEG indices that have been utilized for evaluating the reactions of the people in marketing stimuli: (1) the approach-withdrawal (AW) motivation index; (2) effort index; (3) choice index; and (4) valence. Such indices assist marketers in understanding customer responses to products [30,31].…”
Section: Eeg Indicesmentioning
confidence: 99%
“…Positive AW values correspond to positive motivation (approach behaviors), expressed in terms of the higher activation of the left frontal cortex. In contrast, negative AW values correspond to negative motivation (avoidance behaviors), expressed in terms of the higher activation of the left frontal cortex [29][30][31][32].…”
Section: Aw Indexmentioning
confidence: 99%
See 3 more Smart Citations